Some aspects of the interlanguage of selected freshmen high school students an error analysis - Albarracin, Luz Gabunada 1947-
This research was conducted to investigate some issues pertinent to second language acquisition, particularly the error types committed by the subjects, through the process of inferring the learning strategies. The study was made on the language samples taken from the students' topic controlled compositions, dicto-compositions and free essays. Morpho-syntactic errors occurred more frequently in the interlanguage of the subjects. Lexical errors followed. The errors were attributed to incomplete application of rules, ignorance of rule restrictions, false concepts hypothesized, overgeneralizations, and transfer. This study offered a number of implications and insights for second language learning and teaching.